Data from: The complexity of social complexity: a quantitative multidimensional approach for studies on social organisation - Holland, Jacob; Bloch, Guy (Dryad, 2020)
The rapid increase in “big data” of the post-genomic era makes it crucial
to appropriately measure the level of social complexity in comparative
studies. We argue that commonly-used qualitative classifications lump
together species showing a broad range of social complexity, and falsely
imply that social evolution always progresses along a single linear
stepwise trajectory that can be deduced from comparing extant species. To
illustrate this point, we compared widely-used social complexity measures
in "primitively eusocial" bumble bees with “advanced eusocial”
stingless bees, honey bees, and attine ants. We find that a single species
can have both higher and lower levels of complexity compared to other
taxa, depending on the social trait measured. We propose that measuring
the complexity of individual social traits switches focus from semantic
discussions and offers several directions for progress. Firstly,
quantitative social traits can be correlated with molecular,
developmental, and physiological processes within and across lineages of
social animals. This approach is particularly promising for identifying
processes that influence or have been affected by social evolution.
Secondly, key social complexity traits can be combined into
multidimensional lineage-specific quantitative indices enabling fine scale
comparison across species that are currently bundled within the same level
of social complexity.
(Copied from Methods in ms) To quantify bumble bee queen-worker size
differentiation, we used data from Cumber (1949) and new data. In Cumber’s
publication, wing lengths of females (n = 944) present in nine nests of
six species were provided without distinguishing between workers and
queens. However, all colonies were stated to contain queens and the size
distribution was clearly bimodal in each colony, which we assumed to
represent worker and queen modes. In the pollen-storing species (B.
lapidarius, B. lucorum, B. terrestris, B. pratorum), there was clear
separation of worker and queen distributions. For the pocket-making
species (B. agrorum, B. hortorum), where queen-worker size distinction is
less obvious, the size measurement with the minimum amount of records
between the worker and queen modes (a clear trough in all three colonies)
was assumed to consist of workers and queens equally, with all values
smaller and larger than this assumed to be workers and queens,
respectively. Additional size data using thorax width, was taken from all
emerging workers (n = 434) and gynes (n = 26) in five B. terrestris
colonies kept enclosed in standard laboratory conditions, from incipient
colonies to queen death (de Medici & Bloch, unpublished data). A
B. terrestris value was calculated from both studies using a mean weighted
by sample size.  Queen worker size ratio, queen mean
size / worker mean size, was calculated for comparison with stingless bee
data from Toth et al. (Toth et al., 2004), and attine ant data from
Fergusson-Gow et al (Ferguson-Gow et al., 2014). Additionally, a value for
Apis mellifera was calculated using thorax size, and taking a mean from
European and African strains (DeGrandi-Hoffman et al., 2004). To
statistically compare bumble bees to stingless bees and (separately) to
attine ants, we used species-level Wilcoxon Rank Sum tests (given the
non-normality of the data). For comparing bumble bees and Apis mellifera
(single value only), a Wilcoxon Rank Sum test does not provide sufficient
power to allow such comparisons, thus we assumed a normal distribution and
equal variances in a t test. To quantify bumble bee among-worker size
differentiation, we used the following: B. terrestris data obtained from
i) wing marginal cell length of all workers (n = 1832) produced by nine
freely-foraging colonies over the majority of colony growth (Holland et
al., 2020 preprint); ii) thorax width of all workers (n = 4492) found in
28 freely-foraging colonies around the peak of colony growth (Goulson et
al., 2002), iii) wing length of workers (n = 139) found in wild colonies
(Cumber, 1949). B. impatiens data obtained from thorax width of all
workers (n = 1133) produced by 12 enclosed colonies over the later stages
of colony growth (Couvillon et al., 2010; J. Jandt, personal
communication). Other Bombus spp. data obtained from wing lengths of
workers (n = 570) found in seven wild colonies of five species (Cumber,
1949). For the data from Cumber’s (1949) study, workers were determined as
described above. The coefficient of variation, 100 x (worker head width
standard deviation / worker head width mean), was calculated for
comparison with attine ant data from Fergusson Gow et al. (2014)
meta-study. In addition, stingless bee data from Waddington et al. (1986)
and Gruter et al. (2017) were also used to calculate coefficients of
variation (there was no overlap in the species covered by each study). A
value for Apis mellifera was obtained from Roulston & Cane (2000).
Although size in bumble bees was measured as thorax width or wing marginal
cell length, we assume this to be comparable to head width (which was used
for ants and stingless bees), because both of these measures are strongly
correlated with head width across the full size range of Bombus terrestris
workers (Pearson correlation, thorax width-head width, rho = 0.92, R2 =
0.85;  wing cell length-head width, rho = 0.95, R2 = 0.90; n =
69, Holland unpublished data). To statistically compare bumble bee species
to stingless bees and (separately) to attine ants, we used species-level
Wilcoxon Rank Sum tests (given the non-normality of the data). As with the
Queen-Worker comparison, for comparing bumble bees and Apis mellifera
(single value only), a Wilcoxon Rank Sum test does not provide sufficient
power to allow such comparisons, thus we assumed a normal distribution and
equal variances in a t test. We produced a genus-level phylogenetic tree
for graphical comparison using relationships from the following studies:
within Attini, Fergusson-Gow et al. 2014; within Meliponini, Rasmussen
& Cameron 2009; between Meliponini, Bombini and Apini, Cardinal
& Danforth 2011; between Apidae and Formicidae, numerous studies,
e.g. Johnson et al. 2013. The trees were produced, without differences in
branch length, using TreeGraph2. As an example of comparing social
complexity between species, we chose six species (Apis mellifera, Atta
sexdens, Bombus terrestris, Euglossa viridissima, Melipona fasciata, and
Trachymyrmex septentrionalis) for which quantitative data were available
in five social traits. The traits were quantified as follows: 1) Worker
size variation = log10 coefficient of variation in worker head-width (A.
mellifera = Roulston & Cane 2000; A. sexdens, T. septentrionalis =
Fergusson-Gow et al. 2014; B. terrestris = see above; M. fasciata =
Waddington et al. 1986; E. viridissima = variation among females, Eltz et
al 2011); 2) Queen-worker body size dimorphism = mean queen size / mean
worker size (A. mellifera = deGrandi-Hoffman et al 2004, see above; A.
sexdens, T. septentrionalis = Fergusson-Gow et al. 2014; B. terrestris =
see above; E. viridissima = equal size assumed since all females can mate
and disperse; M. fasciata = Toth et al. 2004); 3) Reproductive skew = the
proportion of adult males which are queen-produced rather than
worker-produced in queenright colonies (A. mellifera, B. terrestris,
Trachymyrmex spp. = Wenseleers & Ratneiks 2006; A. sexdens = 1
implied given no viable worker-laid eggs in Dijkstra et al. 2005; E.
viridissima = the mean proportion of eggs laid by dominant mother, Cocom
Pech 2008; M. fasciata = Toth et al. 2004); 4) Colony size = log10 number
of workers at peak colony size (A. mellifera = approximated at 10,000
workers; A. sexdens, T. septentrionalis = Fergusson-Gow et al. 2014; B.
terrestris = approximated at 200 workers; E. viridissima = Cocom Pech
2008; M. fasciata = Toth et al. 2004); 5) Colony longevity = best estimate
of lifespan in colonies surviving foundation (A. mellifera = mean of feral
colonies, Seeley 1978; A. sexdens = Keller 1998; B. terrestris =
approximated at 0.5 years;  E. viridissima = longevity of adults,
Skov & Wiley 2005; M. fasciata = Roubik 1983; T. septentrionalis =
approximated at 2 years, based on comments in Beshers & Traniello
1996 and Weber 1966). For plotting, traits were rescaled across species,
so that the minimum was set to 0 and the maximum was set to 1. This
rescaling was performed both for all species together (presented in Figure
4A) and for ants and bees separately (Figure 4B, C). To produce the
combined indices (Figure 4B, C), unweighted means of the 6 scaled trait
values were then calculated. This is not an exclusive list of traits that
could be quantified as components of social complexity, and several of
these traits could be quantified by alternative or complementary methods.
These comparisons are obviously limited by the amount of comparable data
available.
(Copied from readme file): Data for Holland & Bloch 2020; The
complexity of social complexity: a quantitative multidimensional approach
for studies on social organisation (American Naturalist) Readme file
WWdata Worker size variation data. Further details in ms. HeadWidth.mean,
ThoraxWidth.mean, Mcell.mean, WingLength.mean = Mean sizes (mm) of workers
taken for either head width, thorax width, wing marginal cell length, or
wing length. NAs indicate unmeasured indicies, or values not given. CV =
coefficient of variation for the size index measured (100 x (sd/mean)).
Source = source of data. Gruter2017 = doi: 10.1038/s41467-016-0012-y;
Waddington1986 = Waddington KD, Herbst LH, Roubik DW, 1986. Relationship
between Recruitment Systems of Stingless Bees and Within-Nest Worker Size
Variation. Journal of the Kansas Entomological Society 59:95-102;
FergusonGow2014 = doi: 10.1098/rspb.2014.1411; Couvillon1949 = data from
Jenny Jandt, relating to study in doi: 10.1111/j.1365-2311.2010.01198.x;
Cumber1949 = doi: 10.1111/j.1365-2311.1949.tb01420.x.; Goulson2002 = doi:
10.1006/anbe.2002.3041; Holland2020 = doi: 10.1101/2020.05.06.079525;
combination = taking a mean value from the three Bombus terrestris
studies, weighted by sample size (Cumber, n = 139, Goulson, n = 4494,
Holland, n = 1832); Roulston2000 = Roulston TaH, Cane JH, 2000. The Effect
of Diet Breadth and Nesting Ecology on Body Size Variation in Bees
(Apiformes). Journal of the Kansas Entomological Society 73:129-142.
QWdata Worker-worker size difference data. Further details in ms. QWratio
= queen mean size / worker mean size. Source = FergusonGow2014 = doi:
10.1098/rspb.2014.1411; Cumber1949 = doi:
10.1111/j.1365-2311.1949.tb01420.x.; MediciBloch = Igor Medici De Mattos
& Guy Bloch, unpublished data; combination = taking a mean value
from the two Bombus terrestris studies, weighted by sample size
(MediciBloch = 460, Cumber, n = 178); Toth2004 = doi:
10.1007/s00040-003-0707-z; DeGrandiHoffman2004 =
10.1603/0013-8746(2004)097[1299:doaiba]2.0.co;2.   quantData Data
from five social traits in six species. Further details, and data sources,
in ms. value = value of metric specified in metric column metric = Qwsize,
queen mean size / worker mean size (i.e. QWratio); PcntMales, the
proportion of adult males which are queen-produced rather than
worker-produced in queenright colonies (i.e. reproductive skew); wCoV,
coefficient of variation in worker size; ColSize, number of workers at
peak colony size; Longevity, best estimate of lifespan in colonies
surviving foundation. scaledValue = value of the metric when rescaled
across values for that metric from all six species, such that lowest value
is 0 and highest value is 1. AntScaledValue = value of the metric when
rescaled across values for that metric from both ant species, such that
lowest value is 0 and highest value is 1. Used to calculate combined index
for ants. BeeScaledValue = value of the metric when rescaled across values
for that metric from all four bee species, such that lowest value is 0 and
highest value is 1. Used to calculate combined index for bees. Cumber
female sizes Data entered from Cumber 1949 (doi:
10.1111/j.1365-2311.1949.tb01420.x.;). Added here for convenience, since
data in the original publication was presented in printed tables only.
Further details in ms.